2014
DOI: 10.1038/cgt.2014.55
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of EGFR inhibits growth and invasion of gastric cancer cells

Abstract: The epidermal growth factor receptor (EGFR) is an oncogenic trans-membranous receptor, which is overexpressed in multiple human cancers. However, the role of EGFR in gastric cancer (GC) is still elusive. In this study, we aimed to investigate the expression and molecular mechanisms of EGFR in GC cells. Forty cases of GC and the corresponding adjacent non-cancerous tissues (ANCT) were collected, and the expression of EGFR was assessed using immunohistochemistry in biopsy samples. Furthermore, EGFR signaling was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…It was reported that upregulation of EGFR expression is associated with lymph node metastases of gastric cancer, and blockade of EGFR signaling suppresses growth and invasion of gastric cancer cells through AKT pathway. 14 We hypothesed that overexpression of Rab11-FIP2 promotes the sustained AKT activation in gastric cancer. Overexpression of Rab11-FIP2 may result in suppression of the internalization of EGFR in COS-7 cells.…”
Section: Overexpression Of Rab11-fip2 Results In Suppression Of the Imentioning
confidence: 99%
“…It was reported that upregulation of EGFR expression is associated with lymph node metastases of gastric cancer, and blockade of EGFR signaling suppresses growth and invasion of gastric cancer cells through AKT pathway. 14 We hypothesed that overexpression of Rab11-FIP2 promotes the sustained AKT activation in gastric cancer. Overexpression of Rab11-FIP2 may result in suppression of the internalization of EGFR in COS-7 cells.…”
Section: Overexpression Of Rab11-fip2 Results In Suppression Of the Imentioning
confidence: 99%
“…This is in line with observation of Zuo et al who showed that pharmacologic inhibition of EGFR activity reduced the production of MMP‐9, as well as squamous carcinoma cell migration and invasion. Zhen et al also indicated that knockdown of EGFR reduced cell invasion of gastric cancer and led to decreased expression of MMP‐9. Interestingly, reduced activity of MMP‐9 was induced by the overexpression of EGFR in A375 cells.…”
Section: Discussionmentioning
confidence: 98%
“…For example, CD24 was shown to support the expression of HER2 and contribute to decrease the sensitivity of HER2-positive breast cancer cells to lapatinib (HER2-targeted therapy) [21]. EGFR, a homodimer of ErbB1, is of particular importance in gastric cancer, as its level of expression is increased during the progression of tumor progression and is correlated with reduced overall survival [22]. In the present study, we investigated the relevance of EGFR expression in CD24 positive gastric cancer.…”
Section: Introductionmentioning
confidence: 99%